GIVE ME BACK MY PONY - Simon,Francesca (Britain: Orion Children's Books, 2012)
Horrid Henry: Sports is a fun and mischievous installment in the Horrid Henry series by Francesca Simon. The book is a collection of short stories centered around Horrid Henry's adventures and misadventures in the world of sports. In the first story, Horrid Henry and the Football Fiend, Henry competes in a soccer match, but his idea of playing is more about causing chaos and annoying everyone than actually trying to win. He repeatedly sabotages his team, leading to hilarious results. In Horrid Henry$1 (Bs School Sports Day, Henry is determined to win at all costs. However, he does everything he can to cheat his way to victory, much to the annoyance of his classmates and teachers. As usual, his plans backfire, and he finds himself in even more trouble.s
"Horrid Henry: Sports" is a lively and humorous book in the Horrid Henry series by Francesca Simon. This collection of short stories revolves around the misadventures of the mischievous and naughty Horrid Henry, who often causes chaos in the world of sports. Known for his bad behavior and lack of sportsmanship, Henry$1 (Bs antics make for entertaining and funny situations that highlight his constant quest to outshine others$1 (Bespecially his goody-two-shoes younger brother, Perfect Peter. The book features several stories in which Henry takes part in various sports competitions, from soccer and school sports days to tennis tournaments. In each story, Henry$1 (Bs approach to sports is less about teamwork and more about his self-centered desire to win by any means necessary, often leading to disaster. He cheats, disrupts, and annoys everyone around him, only to face the consequences of his actions in the end. His plans rarely succeed, and instead of winning, he often ends up in more trouble.s
Keywords: Sportsmanship; Competition